The influence of MgO, Y2O3 and ZrO2 additions on densification and grain growth of submicrometre alumina sintered by SPS and HIP. Issue 8 (September 2015) - Galusek, Dušan; Sedláček, Jaroslav; Chovanec, Jozef; Michálková, Monika
Abstract: Spark plasma sintering followed by hot isostatic pressing was applied for preparation of polycrystalline alumina with submicron grain size. The effect of additives known to influence both densification and grain growth of alumina, such as MgO, ZrO2 and Y2 O3 on microstructure development was studied. In the reference undoped alumina the SPS resulted in some microstructure refinement in comparison to conventionally sintered materials. Relative density >99% was achieved at temperatures >1200 °C, but high temperatures led to rapid grain growth. Addition of 500 ppm of MgO, ZrO2 and Y2 O3 led, under the same sintering conditions, to microstructure refinement, but inhibited densification. Doped materials with mean grain size <400 nm were prepared, but the relative density did not exceed 97.9%. Subsequent hot isostatic pressing (HIP) at 1200 and 1250 °C led to quick attainment of full density followed by rapid grain growth. The temperature of 1250 °C was required for complete densification of Y2 O3 and ZrO2 -doped polycrystalline alumina by HIP (relative density >99.8%), and resulted in fully dense opaque materials with mean grain size<500 nm.